Effectiveness Meniran ( Phyllanthus Niruri Linn ) as Immunomodulation onLymphocyte of Broiler Infected with Enterotoxin Escherichia Coli Resistant Antibiotics - Wahjuni, Retno Sri; Sabdoningrum, Emy Koestanti; Hidanah, Sri (UI Scholars Hub, 2017)
Enterotoxin Escherichia coli resistant to antibiotics on broiler. The used of antibiotics should be re- evaluated, as well as over Escherichia coli enterotoxin. Plants meniran (Phyllanthus niruri Linn) is a plant that can be used as an alternative prevention and treatment of diseases caused by Escherichia coli enterotoxin. In this research, broilers at the age of 23 days were divided into six groups. Two groups are positive control was infected by Escherichia coli and negative control was not infected by Escherichia coli. Three groups are extract of Phyllanthus niruri Linn. plant that variety in three dosage: 20%, 25%, 30% and antibiotic. After five days treatment the broiler was to take the sample of blood tissue. The data were tested with Annova and continued by Duncan multiple range test. There was a significant difference of immunomodulation activity between treatment group doses 30% has been able to decrease lymphocyte on blood. The result showed doses 30% can be used as immunomodulation to Escherichia coli.